A Roadmap for Integrating Neuroscience Into Addiction Treatment: A Consensus of the Neuroscience Interest Group of the International Society of Addiction Medicine - Verdejo-Garcia, A. (Frontiers Media S.A., 2021)
10.3389/fpsyt.2019.00877